Micropropagation and Protoplast Culture in Paraserianthes falcataria - Miyuki Chujo; Junji Eizawa; Shinso Yokota; Kazuya Iizuka; Dody Priadi; Nurul Sumiasri; Nobuo Yoshizawa (Wood Research Journal, 2010)
Paraserianthes falcataria (L.) Nielsen is a fast-growing tree native to Indonesia that has been widely planted throughout the tropics. The growth and wood qualities of P. falcataria should be improved to promote the establishment of plantation forests for this species. Tissue culture technique has a potential to be applied for tree breeding programs for P. falcataria. The objective of this study is to establish the micropropagation and protoplast culture protocol of P. falcataria. In the present study, the respective conditions were investigated for seedling culture, callus induction, protoplast isolation, and protoplast culture. Surface-sterilized seeds were cultured on MS (Murashige and Skoog) medium at 25, 27, and 29°C. After 4 weeks of culture, 27°C gave the best result for average shoot length. Five types of explant (leaflet, petiole, internode, cotyledon, and hypocotyl) obtained from the seedlings were used for callus induction. They were cultured on the MS media containing a combination of 6-benzylaminopurine (BAP) and 2,4-dichlorophenoxyacetic acid (2,4-D) at different concentrations. Green nodular callus was obtained from only leaflet. The most effective medium condition for callus induction from leaflet was the MS medium containing 10.0 µM BAP and 10.0 µM 2,4-D. Leaflet of seedlings was used for protoplast isolation. Based on the results of the yield and viability of protoplasts, the best enzymatic condition was as follows: enzyme solution, 1% Cellulase Onozuka RS, 0.5% Pectolyase Y-23, and 1% Driselase; osmoticum, 0.8 M mannitol; treatment temperature and time, 30°C for 4 hrs. Isolated protoplasts were incubated in liquid AA media with a combination of 1-naphthaleneacetic acid and thidiazuron at different concentrations. Although cell wall formation was observed, cell division did not occur.